2015
DOI: 10.4236/ojn.2015.51007
|View full text |Cite
|
Sign up to set email alerts
|

Critical Factors in Managing Relationally Demanding Jobs, in Care for Very Ill and/or Dying Patients: A Phenomenological Study among Public Hospital Nurses

Abstract: Background: Workload, interpersonal relationships, professional conflict and the emotional cost of providing care are potential sources of stress and burnout among nurses. Based on experiences of hospital nurses, this paper aims to identify critical factors for nurses in managing relationally demanding situations in care for very ill and/or dying patients. Methods: In-depth interviews were carried out with six nurses, working in a medium-sized hospital in Norway. The interviews were analysed using an interpret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…The dominating approach towards authenticity is to understand autonomous acts as being authentic acts; that is, the action springs from values, wishes or motivations which the persons identify with [32]. Several studies have shown that the consequence of not identifying with an activity, or not feeling competent to perform it, may have contributed to the symptoms of burnout and problems in maintaining their health over time [34]- [36]. When the nurses act in accordance with their own values and interests, they can avoid feeling the stress that is often connected with acts of inauthenticity and thus gain positive health benefits.…”
Section: Discussionmentioning
confidence: 99%
“…The dominating approach towards authenticity is to understand autonomous acts as being authentic acts; that is, the action springs from values, wishes or motivations which the persons identify with [32]. Several studies have shown that the consequence of not identifying with an activity, or not feeling competent to perform it, may have contributed to the symptoms of burnout and problems in maintaining their health over time [34]- [36]. When the nurses act in accordance with their own values and interests, they can avoid feeling the stress that is often connected with acts of inauthenticity and thus gain positive health benefits.…”
Section: Discussionmentioning
confidence: 99%